Cover Image. Issue 9 (17th May 2021) - Liu, Xiqin; Lai, Han; Li, Jingguang; Becker, Benjamin; Zhao, Yajun; Cheng, Bochao; Wang, Song
Abstract : COVER ILLUSTRATION The meta‐analytic morphological variations in the bilateral dACC/mPFC (illustrated as the red brain area) were consistently associated with interindividual differences in neuroticism. Individuals who are highly neurotic, characterized by general tendency to negative emotions and thoughts (illustrated as the cobweb), have greater gray matter volume in the bilateral dACC/mPFC than people who are less neurotic.